Soil quality under acacia mangium plantation in Nanga Lajan, Song - Cartina Luyau, Anak Sulau (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Acacia mangium is widely planted as plantation species in Sarawak due to rapid changing in deforestation activities such as logging and clear cutting henceforth to accommodate the supply of raw material timber for industrial purposes. A. mangium has been chosen as a number one species planted in Sarawak for reforestation because it is adaptive to the infertile habitat and also proven to be fast growing species · In order to understand the soil fertilities changes in A. mangium plantation, the soil physical and chemical properties before and after harvesting A. mangium were carried out. Therefore the objective of this study is to clarify the soil quality parameters in established A. mangium in both areas. The soil profile of the study areas were examined in situ for both harvested and non harvested A. mangium aged 10 years old. The soil samples also been taken in two depth which is 0 to 10 cm and 20 to 30 cm depth for soil composite analysis. The results showed that the soil profile composed of 0, BA, Bland B2 horizon for both areas. The status of soil under establishment of A. mangium was clarified in this study. Laboratory results for the soils indicated that the soil pH at both study areas to be acidic and the readings increased with the increasing depth. The soil organic matter in the upper horizon was indicated to be higher and contributed to the higher organic nutrients in the BA horizon, thus improved the fertility status of the soil. The total carbon in 20 to 30 cm depth between harvested and non harvested area showed a significant different using Student's t-test. Meanwhile, no other significant different between both chemical and physical analysis in both depths and areas such as pH, electric conductivity, porosity, water content, bulk density, moisture content and aluminum. Nevertheless, the A. mangium plaRtation could significantly improve soil structure and moisture condition, improve the content of soil organic matter and nutrients, prevent soil degradation and protect eco-environment, which was advantageous to the sustainable development of forest plantation.